Husband Involvement in Safe Motherhood Services among Married Women of Bharatpur Sub Metropolitan City, Chitwan - Chapagain, Shakuntala; Chhetri, Muniraj; Dhungana, Govinda Prasad (Journal of Chitwan Medical College, 2019)
Background: Safe motherhood means creating the circumstances within which a woman is able to choose whether she become pregnant and if she does, ensuring that she receives care for preventive and treatment of pregnancy complication. This study was aimed to find out husband involvement in safe motherhood services and its associated factor. Methods: Community based cross-sectional study was conducted in purposively selected Bharatpur sub metropolitan city of Chitwan district. Among 29 wards, three wards (2, 11, and 15) were selected by using simple random sampling method. Bivariate analysis was done to find out the factors, and significant factors in bivariate analysis, were further analyzed in multivariate to see the association between outcomes variables. Results: Husband involvement in family planning (FP), antenatal care (ANC), and childbirth were found to be 10.5%, 52.2% and 78.7% respectively. In multivariate analysis, safe motherhood news listened by husband (AOR 9.813, CI: 4.854 - 19.839) was found statistically associated with husband involvement in antenatal care services. In multivariate analysis, husband who had engaged in business, service and farming/daily wages was found 20.668 (CI: 7.740 – 55.192), 13.058 (CI: 5.818 – 29.310) and 14.195 (CI: 4.139 – 48.674) times more likely involved during child birth respectively than those who had engaged in foreign job. Conclusions: Husband education on safe motherhood issues, employment opportunity within country and women decision-making power should be a significant part of strategies for increasing husband involvement in safe motherhood services.